A descriptive study of the health information needs of Kenyan women in the first 6 weeks postpartum - Everlyne Rotich; Liz Wolvaardt (BMC, 2017)
Abstract Background A large number of maternal and neonatal deaths occur during birth and 48 h after birth. The benefits of postnatal care to the mother and newborn cannot be overemphasized as this is another opportunity where complications that might arise from pregnancy and childbirth can be treated, as well as the time to provide important information on maternal and newborn care after delivery. This study aimed to determine the information needs of mother-baby pairs in the first 6 weeks after birth. Methods An exploratory qualitative study using in-depth interviews at three points in time was conducted with 15 women who had their births at Moi Teaching and Referral Hospital, Kenya. The first interview was done within 48 h after birth followed by a telephone interview at 2 weeks and at 6 weeks after birth. Data were audio recorded and transcribed. Transcripts and field notes were analyzed using thematic content analysis and NVIVO 11 software. Ethical approval was obtained before commencement of studies and permission to conduct the study granted by the chief executive of the hospital. Results The only health needs that participants reported were unmet health information needs. Four major themes emerged from the study. 'Connecting with baby' centered on understanding and meeting baby's needs, monitoring growth and progress and protecting the baby. The second theme: "Birth as a unique encounter' is a blend of what was found to be new and a unique. The theme 'Regaining self' is a combination of managing self as a mother and handling discomfort related to birth. The final theme: 'Disconnected information' is a collection of unmet information needs, the need for clarity in information booklets and conflicting information by different providers. Conclusions Participants used the hospital stay as an opportunity to receive more detailed information on how to take care of their babies both directly after birth and in the longer term. Participants had a range of unmet health information needs that extended beyond family planning and fertility. Needs extended to their own care and management of discomforts. The need for consistency in health information by different providers and updated printed material on postnatal care that includes sensitive information and allows opportunities for personalized information was highlighted.